Analisa SWOT-AHP untuk Penentuan Strategi Pembelajaran Proyek dalam Pengembangan Pendidikan Karakter pada Sekolah Menengah Atas di Kabupaten Kapuas - Merliana, Ni Putu Eka; Widyantara, I Made Oka; Wirastuti, Ni Made Ary Esta Dewi; Saputra, Komang Oka; Widyanto, I Putu (Cetta: Jurnal Ilmu Pendidikan, 2025)
The project-based learning model is one of the strategies used to increase student engagement and motivation, especially in supporting the development of character education. However, in its application, project learning faces challenges such as taking a long time, causing students to feel bored, and not all students are fully and evenly active in the learning process. This has an impact on the non-achievement of learning objectives in the development of character education. This study aims to identify the factors needed to improve the quality of project learning implementation for character education development. The strategy analysis used in the study uses external as well as internal factors analysis with SWOT and AHP (Analytic Hierarchy Process). The method used in this study is a mixed method with an exploratory sequential design, which collects data qualitatively, namely through interviews and observations, which are then followed by quantitative analysis by distributing questionnaires to respondents. The results show that internal factors, namely innovative and digitalized school management, are the main strengths in implementing project learning for character education development. On the other hand, external factors show significant opportunities for driving schools to support this learning while considering external threats. The top priority strategy recommended in character education development is to utilize technology for innovative learning that increases student engagement. This strategy aims to provide space for students to make progress in cognitive, affective and psychomotor aspects. The main focus in project learning is to ensure students are actively engaged, so an innovative, technology-based approach is needed that allows students to explore, think critically and develop themselves.